2015
DOI: 10.1039/c5fo00214a
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nrf2 target enzymes conferring protection against oxidative stress in PC12 cells by ginger principal constituent 6-shogaol

Abstract: Natural compounds containing phenoxyl groups and/or Michael acceptor units appear to possess antioxidant and cytoprotective properties. The ginger principal constituent 6-shogaol (6-S) represents one of such compounds. In this study, we reported that 6-S efficiently scavenges various free radicals in vitro, and displays remarkable cytoprotection against oxidative stress-induced cell damage in the neuron-like rat pheochromocytoma cell line, PC12 cells. Pretreatment of PC12 cells with 6-S significantly upregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 59 publications
(119 reference statements)
0
52
0
Order By: Relevance
“…The compounds containing Michael acceptors are usually precluded in the process of traditional drug design due to Michael acceptors have the ability to react with various electron‐rich biomolecules. However, growing evidences have supported that drugs with Michael acceptors can become effective activators of Nrf2 signaling pathway , highlighting that Michael acceptor is a promising pharmacophore in parts of cytoprotective drugs. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The compounds containing Michael acceptors are usually precluded in the process of traditional drug design due to Michael acceptors have the ability to react with various electron‐rich biomolecules. However, growing evidences have supported that drugs with Michael acceptors can become effective activators of Nrf2 signaling pathway , highlighting that Michael acceptor is a promising pharmacophore in parts of cytoprotective drugs. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Study by Moon et al (2014) [20] revealed that administration of 6-shogaol significantly enhanced learning and memory in both memory-impaired and normal mice. A recent study by Peng et al (2015) [21] reported that 6-shogaol possessed anti-oxidant and cytoprotective effects against oxidative stress-induced cell damage in PC-12 cells. Peng et al (2015) [21] further suggested that 6-shogaol may be a potential candidate for the prevention of oxidative stress-mediated neurodegenerative disorders.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Peng et al (2015) [21] reported that 6-shogaol possessed anti-oxidant and cytoprotective effects against oxidative stress-induced cell damage in PC-12 cells. Peng et al (2015) [21] further suggested that 6-shogaol may be a potential candidate for the prevention of oxidative stress-mediated neurodegenerative disorders. However, to date, there are limited reports on the neuritogenic activity of the chemical compounds isolated from common ginger, notably 6-shogaol.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, age-related impairments ultimately converge to negatively impact cell respiration, which manifests as the overproduction of reactive oxygen species (ROS). Oxidative stress is defined as an imbalance between the production of ROS or reactive nitrogen species (RNS) and the production of antioxidants (2). For this reason, oxidative stress has become the one of the main targets for the treatment of neurological diseases (3).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to exert antioxidant protective effects against Pb-induced hepatotoxicity (11), and to exert significant beneficial effects on sperm viability, motility and serum total testosterone levels due to its antioxidant effects (12). [6]-Shogaol is a novel small molecule activator of nuclear factor (erythroid-derived 2)-like 2 (Nrf2) in PC12 cells, and therefore, it is a potential candidate for the prevention of oxidative stress-mediated neurodegenerative disorders (2). Furthermore, cysteine-conjugated shogaols in ginger have been found to induce apoptosis via an oxidative stress-mediated p53 pathway in human colon cancer cells (13).…”
Section: Introductionmentioning
confidence: 99%